Optical Imaging Approaches to Monitor Static and Dynamic Cell‐on‐Chip Platforms: A Tutorial Review. Issue 28 (14th May 2019) - Arandian, Alireza; Bagheri, Zeinab; Ehtesabi, Hamide; Najafi Nobar, Shima; Aminoroaya, Neda; Samimi, Ashkan; Latifi, Hamid
Abstract: Miniaturized laboratories on chip platforms play an important role in handling life sciences studies. The platforms may contain static or dynamic biological cells. Examples are a fixed medium of an organ‐on‐a‐chip and individual cells moving in a microfluidic channel, respectively. Due to feasibility of control or investigation and ethical implications of live targets, both static and dynamic cell‐on‐chip platforms promise various applications in biology. To extract necessary information from the experiments, the demand for direct monitoring is rapidly increasing. Among different microscopy methods, optical imaging is a straightforward choice. Considering light interaction with biological agents, imaging signals may be generated as a result of scattering or emission effects from a sample. Thus, optical imaging techniques could be categorized into scattering‐based and emission‐based techniques. In this review, various optical imaging approaches used in monitoring static and dynamic platforms are introduced along with their optical systems, advantages, challenges, and applications. This review may help biologists to find a suitable imaging technique for different cell‐on‐chip studies and might also be useful for the people who are going to develop optical imaging systems in life sciences studies. Abstract : Cell‐on‐chip platforms promise various applications in biology. In cell‐chip studies, the demand for direct monitoring is rapidly increasing. In this review, various optical imaging approaches are briefly discussed. The discussion focuses on their optical systems, advantages, limitations, and examples of applications. The practical viewpoint of this study might be useful for researchers in optics and biology.